Filhos, saúde e migração: o processo migratório de mulheres angolanas para a cidade de São Paulo - Novaes, Dirce Trevisi Prado (2021)
The aim of this study is to understand and map the migratory strategies used by the Angolan women as part of their migratory projects, mainly considering the migrating regulation for their Brazil- born children and also the better conditions of health and education for them, their children and families. For this purpose it was conducted a case study among Angolan women who came to São Paulo, pregnant or not, with children or not, together with married / unmarried husbands or not, during the period from 2013 to 2018. As a methodology, it was made a bibliographic review of articles as well as dissertations and thesis which address migration, maternity, female migration and Angolan migration to Brazil. One of the main theoretical references was the concept of the “Feminization of Migration”. Moreover, semi structured in depth interviews were conducted with nineteen Angolan women who arrived in São Paulo after 2013, in order to research and identify the personal characteristics, the reasons for displacement and the strategies used to migrate. Interviews took place mostly at institutions that assist migrant women in São Paulo, after explanation and signatures on the consent form. To complement the search, fourteen specialists were also interviewed: Angolan PhD researchers and professionals from Institutions that attend these women and children in São Paulo. The contents resulting from these interviews were grouped into categories such as: demographic and origin issues; migration Angola – Brazil; maternity, children and family; education; health; socialization and integration in São Paulo; relationship with Angola after migration. We conclude that the purpose of the Angolan women coming to Brazil is to raise their children based on the free and good quality health and education conditions in Brazil. The search for work was not the previous motivation for immigration; it becomes the predominant factor only after the birth and insertion of their children in day-care centers and schools. Furthermore, during the research it was possible to notice that the regulation on Brazilborn children (established in the Statute of the Foreigner 6.815/1980, in the 1988 Federal Constitution, in the Statute of the Child and Adolescent 8.069/1990 and the Migration Law 13.445/2017) was a relevant issue in the strategies of most women, considering that fourteen of the nineteen women who migrated were pregnant, six of them in the 8th month of pregnancy and one was in the 9th. While discussing the subject with the interviewees, we found they did not master the regulation theme but they were sure that by being the mother of a child born in Brazil, their regulation and permanence in Brazil would be guaranteed, even if the means were not understood in depth. This research intends to broaden the understanding of the demands of migrant women, who are often responsible for single - parent families, during their period of pregnancy and the process of raising their children in Brazil, and thus provide greater subsidies for Public and Private Organizations to better offer services to them and their children, whether they are Brazilian or not. Likewise, this thesis aims to contribute to highlight other facets of the migratory movements that are not related only to the male figure and the search for work. We intend to reveal different aspects of the phenomenon of Female Migration in which women are more and more the agents of their migratory processe